Polyunsaturated fatty acids-rich dietary lipid prevents high fat diet-induced obesity in mice - Haneishi, Yuri; Furuya, Yuma; Hasegawa, Mayu; Takemae, Hitoshi; Tanioka, Yuri; Mizutani, Tetsuya; Rossi, Mauro; Miyamoto, Junki (Scientific reports, 2023)
Diet is the primary factor affecting host nutrition and metabolism, with excess food intake, especially high-calorie diets, such as high-fat and high-sugar diets, causing an increased risk of obesity and related disorders. Obesity alters the gut microbial composition and reduces microbial diversity and causes changes in specific bacterial taxa. Dietary lipids can alter the gut microbial composition in obese mice. However, the regulation of gut microbiota and host energy homeostasis by different polyunsaturated fatty acids (PUFAs) in dietary lipids remains unknown. Here, we demonstrated that different PUFAs in dietary lipids improved host metabolism in high-fat diet (HFD)-induced obesity in mice. The intake of the different PUFA-enriched dietary lipids improved metabolism in HFD-induced obesity by regulating glucose tolerance and inhibiting colonic inflammation. Moreover, the gut microbial compositions were different among HFD and modified PUFA-enriched HFD-fed mice. Thus, we have identified a new mechanism underlying the function of different PUFAs in dietary lipids in regulating host energy homeostasis in obese conditions. Our findings shed light on the prevention and treatment of metabolic disorders by targeting the gut microbiota.